2019
DOI: 10.1521/aeap.2019.31.2.127
|View full text |Cite
|
Sign up to set email alerts
|

Condomless Group Sex Is Associated With HIV Pre-Exposure Prophylaxis Knowledge and Interest Uptake: A Cross-Sectional Study of Gay and Bisexual Men in Paris, France

Abstract: As a prevention strategy, HIV pre-exposure prophylaxis (PrEP) may benefit men who participate in group sex, but little is known about PrEP among this group internationally and virtually nothing is known of the European context. This study used an online survey of gay men living in Paris, France to assess associations between group sex and awareness of, use and interest in PrEP in its once-daily, episodic, injectable, and microbicidal forms. Men reporting recent (within 3 months) condomless group sex were much … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
5
1
Order By: Relevance
“…In fact, HIV serodiscordant couples in these settings appeared to modestly decrease HIV risk-related sexual behaviors within the couple in the month following PrEP initiation, and then maintain these lower levels of HIV risk-related sexual behaviors with the couple over time. This finding is different than studies among MSM in high-income countries, which have observed sexual risk compensation following PrEP initiation [7][8][9][10][11]. It is consistent, however, with the study among heterosexual HIV serodiscordant couples enrolled in an open-label extension to a PrEP efficacy trial, which found no evidence of sexual risk compensation following PrEP initiation in Kenya and Uganda [14].…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…In fact, HIV serodiscordant couples in these settings appeared to modestly decrease HIV risk-related sexual behaviors within the couple in the month following PrEP initiation, and then maintain these lower levels of HIV risk-related sexual behaviors with the couple over time. This finding is different than studies among MSM in high-income countries, which have observed sexual risk compensation following PrEP initiation [7][8][9][10][11]. It is consistent, however, with the study among heterosexual HIV serodiscordant couples enrolled in an open-label extension to a PrEP efficacy trial, which found no evidence of sexual risk compensation following PrEP initiation in Kenya and Uganda [14].…”
Section: Discussioncontrasting
confidence: 79%
“…There is emerging evidence that sexual risk compensation following PrEP initiation may occur among men who have sex with men (MSM) in high-income countries [7][8][9][10][11]. Some studies, primarily from cohorts of MSM on PrEP, have shown that PrEP initiation increases the frequency of condomless sex [7-9, 12, 13], number of sexual partners [8,9,11], and the incidence of STIs [10], among members of HIV at-risk populations. A previous study among heterosexual 1 3 HIV serodiscordant couples, enrolled in an open-label extension to a PrEP efficacy trial in sub-Saharan Africa, the Partners PrEP Study, found no evidence of sexual risk compensation following PrEP initiation [14].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, previous studies have predominantly examined the association between group sex participation and HIV/STI acquisition with few data on the details of sexual activities during the group sex event such as the size of the group sex event (i.e., the number of participants) and the sexual activities involved during group sex. Furthermore, the majority of studies collected and reported condom use during group sex as a binary variable (yes or no) ( 2 , 4 , 5 ) and it is unclear whether the participants used a new condom when they changed partners. Using the same condom for more than one partner during group sex increases the risk of STI and HIV transmission between partners ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, only one study has investigated whether MSM changed condoms in between switching partners during group sex, which was undertaken in the United States ( 7 ), while none have explored this practice among FSWs. As previous studies have estimated that almost half of FSWs participate in group sex but no previous studies have extensively investigated the sexual activities and practices during these sex events among FSWs, further exploration into the risks of group sex participation in this population is required to further guide safe sex practices ( 2 , 4 , 5 ). Therefore, we aimed to explore characteristics of group sex among FSWs, including the number of people involved, sexual activities and condom use in between switching partners.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Most studies report condom use in group sex as a binary variable (yes/no) and it is unclear whether participants change condoms for each partner. 4,7 To our knowledge, there has been only one study investigating whether MSM have changed condoms between partners during group sex 4 and there are no quantitative studies among the heterosexual population. Past studies have highlighted the need for further research assessing condom use specifically for mixed-gender group sex events.…”
Section: Introductionmentioning
confidence: 99%